Chemical screening pipeline for identification of specific plant autophagy modulators - Dauphinee, Adrian N; Cardoso, Catarina; Minina, Alyona (Plant physiology, 2019)
Autophagy is a major catabolic process in eukaryotes with a key role in homeostasis, programmed cell death, and aging. In plants, autophagy is also known to regulate agronomically important traits such as stress resistance, longevity, vegetative biomass, and seed yield. Despite its significance, there is still a shortage of reliable tools modulating plant autophagy. Here, we describe the first robust pipeline for identification of specific plant autophagy-modulating compounds. Our screening protocol comprises four phases: (1) high-throughput screening of chemical compounds in cell cultures of tobacco (Nicotiana tabacum); (2) confirmation of the identified hits in planta using Arabidopsis (Arabidopsis thaliana); (3) further characterization of the effect using conventional molecular biology methods; and (4) verification of chemical specificity on autophagy in planta. The methods detailed here streamline the identification of specific plant autophagy modulators and aid in unraveling the molecular mechanisms of plant autophagy.